2011
DOI: 10.1039/c1ib00032b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic physical properties of dissociated tumor cells revealed by dielectrophoretic field-flow fractionation

Abstract: Metastatic disease results from the shedding of cancer cells from a solid primary tumor, their transport through the cardiovascular system as circulating tumor cells (CTCs) and their engraftment and growth at distant sites. Little is known about the properties and fate of tumor cells as they leave their growth site and travel as single cells. We applied analytical dielectrophoretic field-flow fractionation (dFFF) to study the membrane capacitance, density and hydrodynamic properties together with the size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 61 publications
2
65
0
Order By: Relevance
“…21 The isolation of rare cancer cells from blood in particular exploits differences in dielectric properties between blood cells (lymphocytes, monocytes, and granulocytes) and cancer cells. 19,20 For the separation of cancer cells from healthy blood cells, the ApoStream device operates in a modified form to conventional DEP-FFF, in that the cancer cells are attracted by positive DEP forces towards the electrode plane, and thus away from the bulk of the blood cells that are levitated by negative DEP into the hydrodynamic flow velocity profile. This is accomplished by applying the voltage signal at a frequency in between the so-called DEP crossover frequency of cancer cells and PBMCs.…”
Section: Theory and Device Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The isolation of rare cancer cells from blood in particular exploits differences in dielectric properties between blood cells (lymphocytes, monocytes, and granulocytes) and cancer cells. 19,20 For the separation of cancer cells from healthy blood cells, the ApoStream device operates in a modified form to conventional DEP-FFF, in that the cancer cells are attracted by positive DEP forces towards the electrode plane, and thus away from the bulk of the blood cells that are levitated by negative DEP into the hydrodynamic flow velocity profile. This is accomplished by applying the voltage signal at a frequency in between the so-called DEP crossover frequency of cancer cells and PBMCs.…”
Section: Theory and Device Setupmentioning
confidence: 99%
“…19,20 In these earlier studies, DEP-FFF was applied using a batch mode configuration that limited the number of cells processed in a given run because cells must remain spaced by several diameters to avoid dipole-dipole interactions that can perturb DEP responses. 19,21 As a result, the loading capacity using the batch mode of operation was limited to less than a million cells per run and required processing of multiple batches in order to complete a CTC analysis for a typical 7.5 ml blood sample.…”
mentioning
confidence: 99%
“…Because the time constant associated with this relaxation is approximately proportional to the product of specific membrane capacitance and cell radius, the observed decrease in crossover frequency is explainable due to the observed increase in median cell radius and in median specific membrane capacitance of the gemcitabineresistant sub-clones (Table I). Wang et al, 41 Shim et al, 8 and Gascoyne et al 42 attribute higher specific membrane capacitances to larger effective membrane areas due to ruffles and folds in the membrane, changing the apparent effective specific capacitance. Alternatively, Gagnon et al 43 FIG.…”
Section: Resultsmentioning
confidence: 99%
“…According to Wang et al, 41 Shim et al, 8 and Gascoyne et al, 42 this increase in surface area would putatively change the ruffles and folds in the cell membrane, increasing their effective surface area and specific membrane capacitance. Furthermore, Salmanzadeh et al 49 and Mulhall et al 50 observed that aggressiveness of cancer cell phenotype correlates with an increase in specific membrane capacitance for mouse ovarian surface epithelial and oral cancer cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation